2012
DOI: 10.1088/0953-8984/24/50/503101
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of protein unfolding at interfaces

Abstract: The conformation of protein molecules is determined by a balance of various forces, including van der Waals attraction, electrostatic interaction, hydrogen bonding, and conformational entropy. When protein molecules encounter an interface, they are often adsorbed on the interface. The conformation of an adsorbed protein molecule strongly depends on the interaction between the protein and the interface. Recent time-resolved investigations have revealed that protein conformation changes during the adsorption pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 173 publications
4
83
0
Order By: Relevance
“…Native BSA decreased the surface tension of water (buffer only, about 69 mN/m) with increasing protein concentration due to an amphiphilic effect (Kim et al, 2010). In addition, BSA adsorbed very rapidly on the air-water interface and partially unfolded upon adsorption, because BSA was categorized as soft protein, showing reduction of surface tension (Yano, 2012). At a protein concentration of 1mg/ml, native BSA lowered surface tension of aqueous buffer (water) to 57.05 ± 2.92 mN/m, 56.40 ± 0.87 mN/m and 58.71 ± 1.60 mN/m at pH 3, pH 5, and pH 7, respectively.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Native BSA decreased the surface tension of water (buffer only, about 69 mN/m) with increasing protein concentration due to an amphiphilic effect (Kim et al, 2010). In addition, BSA adsorbed very rapidly on the air-water interface and partially unfolded upon adsorption, because BSA was categorized as soft protein, showing reduction of surface tension (Yano, 2012). At a protein concentration of 1mg/ml, native BSA lowered surface tension of aqueous buffer (water) to 57.05 ± 2.92 mN/m, 56.40 ± 0.87 mN/m and 58.71 ± 1.60 mN/m at pH 3, pH 5, and pH 7, respectively.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Extensive researches have been performed to gain insight into interfacial protein structures and properties using a number of techniques, such as surface plasmon resonance (Yano, 2012), nuclear magnetic resonance (NMR) (Judge & Watts, 2011), atomic force microscopy (Fotiadis, 2012), and so on. The applications of these techniques (and others) to the study of the interactions between proteins and surface can be found in previous review articles (Fotiadis, 2012;Judge & Watts, 2011;Yano, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such limitations can lead to misinterpretations of apparent interfacial phenomena, which are used to explain the biocompatibility of biomaterials. For example, conventional biophysical methods often find that the average surface protein conformation relaxes from native-like to nonnative-like upon surface adsorption, which is interpreted as evidence for unfolding (11)(12)(13)(14). However, the time scales over which these conformational changes reportedly occur are orders of magnitude longer than typical surface residence times of isolated proteins (15), suggesting that the picture of surfaceinduced spreading may be oversimplified.…”
mentioning
confidence: 99%